The Impact of Artificial Intelligence on Job Loss: Risks for Governments - Soueidan, Mohamad Hassan; Shoghari, Rodwan (Technium Social Sciences Journal, 2024)
The rapid advancement of Artificial Intelligence (AI) technologies presents both opportunities and challenges for labor markets globally. By adopting a qualitative methodology, this study analyses the impact of AI integration in jobs on the labor market and the subsequent policy responses by governments. The study specifies the industries and jobs that are highly susceptible to AI-driven automation, particularly those characterized by routine and repetitive tasks. The study also acknowledges the potential for AI to create new job categories. Key findings suggest that while AI poses a significant risk of job displacement in several sectors, it also offers opportunities for economic growth, opening of new jobs and innovation. Moreover, the study highlights various government strategies employed globally, including up-skilling and re-skilling initiatives, strengthening social protection systems, and fostering AI-human collaboration. These strategies aim to mitigate the adverse impacts of AI on employment and ensure a balanced transition to AI-integrated economies. Based on these strategies, the paper suggests some recommendations for governments to address AI-driven job losses, emphasizing the importance of multidisciplinary education, ethical AI use, inclusive growth strategies, and international cooperation.